Meningkatkan Kreativitas Seni Anak - Anak Desa Dogang melalui Sosialisasi Pembuatan Gelang dari Tali Koor - Jamiah Nurhakiki; Marshanda Suraya; Nursania Simbolon; Vina Aliana; Siti Maysarah (Lembaga Pengembangan Kinerja Dosen, 2026)
Artistic creativity is an essential aspect of child development, contributing to imagination, fine motor skills, and self-confidence. However, limited access to art-based activities and excessive gadget use have reduced opportunities for children to develop creativity, particularly in rural areas such as Dogang Village, Langkat Regency. This community service program aimed to enhance children’s artistic creativity through the socialization of bracelet-making using paracord as a form of simple and practical non-formal education. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving children who participated in the activity. The socialization process included the introduction of tools and materials, demonstrations of basic knotting techniques, and hands-on practice with direct assistance. The results indicated that participants were able to master several basic techniques, including simple knots, braided patterns, and double (cobra) knots, which contributed to improved creativity, precision, social interaction, and self-confidence. In addition to its educational impact, the bracelets produced demonstrated economic potential, with an affordable selling price starting from Rp.5,000 per unit. Therefore, this activity not only supports the development of children’s artistic creativity but also provides opportunities for sustainable micro-enterprise development within the local community.